Combining Ixazomib With Subcutaneous Rituximab and Dexamethasone in Relapsed or Refractory Waldenström's Macroglobulinemia: Final Analysis of the Phase I/II HOVON124/ECWM-R2 Study. Issue 1 (1st January 2022) - Kersten, Marie José; Amaador, Karima; Minnema, Monique C.; Vos, Josephine M. I.; Nasserinejad, Kazem; Kap, Marcel; Kastritis, Efstathios; Gavriatopoulou, Maria; Kraan, Willem; Chamuleau, Martine E. D.; Deeren, Dries; Tick, Lidwine W.; et al.
Abstract : PURPOSE: Proteasome inhibitors are effective in Waldenström's macroglobulinemia (WM) but require parenteral administration and are associated with polyneuropathy. We investigated efficacy and toxicity of the less neurotoxic oral proteasome inhibitor ixazomib combined with rituximab, in patients with relapsed WM. METHODS: We conducted a multicenter phase I/II trial with ixazomib, rituximab, and dexamethasone (IRD). Induction consisted of eight cycles IRD wherein rituximab was started in cycle 3, followed by rituximab maintenance. Phase I showed feasibility of 4 mg ixazomib. Primary end point for phase II was overall response rate (ORR [≥ minimal response]) after induction. RESULTS: A total of 59 patients were enrolled (median age, 69 years; range, 46-91 years). Median number of prior treatments was 2 (range, 1-7); 70% had an intermediate or high WM-IPSS (International Prognostic Scoring System for WM) score. After eight cycles, ORR was 71% (42 out of 59) (14% very good partial response [PR], 37% PR, and 20% minor response). Depth of response improved until month 12 (best ORR 85% [50 out of 59]: 15% very good PR, 46% PR, and 24% minor response). Median duration of response was 36 months. The average hematocrit level increased significantly (0.33-0.38 L/L) after induction ( P < .001). After two cycles of ixazomib and dexamethasone, immunoglobulin M levels decreased significantly (median 3, 700-2, 700 mg/dL, P < .0001). Median time to first response was 4 months. Median progression-free survival and overall survival were not reached. After median follow-up of 24 months (range, 7.4-54.3 months), progression-free survival and overall survival were 56% and 88%, respectively. Toxicity included mostly grade 2 or 3 cytopenias, grade 1 or 2 neurotoxicity, and grade 2 or 3 infections. No infusion-related reactions or immunoglobulin M flare occurred with use of subcutaneous rituximab. Quality of life improved significantly after induction. In total, 48 patients (81%) completed at least six cycles of IRD. CONCLUSION: Combination of IRD shows promising efficacy with manageable toxicity in patients with relapsed or refractory WM. Abstract :